Some Advanced Functionalities of Optical Amplifiers - Kumar Garai, Sisir (IntechOpen, 2015)
With the explosion of information traffic, the role of optical amplifiers becomes very significant in fulfilling the demand of faster optical signals and data processing in the field of communication. This book covers different advanced functionalities of optical amplifiers as well as their emerging applications in optical communication networks. The first chapter deals with an efficient and validated time-domain numerical modelling of semiconductor optical amplifiers (SOAs) and SOA-based circuits, while the second chapter is based on the working of gallium nitride-based semiconductor optical amplifiers. The role of SOAs for the next generation of high-data-rate optical packet-switched network is presented in Chapter 3. Chapter 4 covers the all-optical semiconductor optical amplifier based on quantum dots (QD-SOA) and its function as an arithmetic processor. In Chapter 5, the authors have presented the role of SOAs in intensity modulation of the optical pulses and their use in deterministic timing jitter and peak pulse power equalization analysis. In Chapter 6, the investigation of broadband S-band to L-band erbium-doped fibre amplifier (EDFA) module is presented, and Chapter 7 includes the optimized design technique of Yb3+/Er3+-codoped phosphate microring resonator amplifiers. All selected chapters are very interesting and well organized, and I hope they will be of great value to postgraduate students, researchers, academics and anyone seeking to understand the advanced functionalities of optical amplifiers in the present scenario.